2016
DOI: 10.1080/03019233.2016.1152344
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental research on iron coke hot briquette – A new type burden used in blast furnace

Abstract: In order to improve blast furnace efficiency, reduce CO 2 emission and accelerate energy utilisation, a new preparation process of iron coke hot briquette (ICHB) based on the raw materials conditions in China, a new type blast furnace ironmaking burden, was experimentally investigated in this paper. The new preparation process was researched and optimised through single factor experiment and orthogonal experiment. Meanwhile, the reactivity and the post-reaction strength of ICHB prepared under the optimised con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Therefore, the utilization of iron coke has great significance for steel industry in China to reduce carbon emission and energy consumption. Based on the Chinese raw material and fuel conditions, the preparation process of iron coke hot briquette (abbreviation ICHB) was proposed in previous work . In this study, the gasification reaction behavior of ICHB was experimentally investigated in the temperature range of 950–1100 °C under isothermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the utilization of iron coke has great significance for steel industry in China to reduce carbon emission and energy consumption. Based on the Chinese raw material and fuel conditions, the preparation process of iron coke hot briquette (abbreviation ICHB) was proposed in previous work . In this study, the gasification reaction behavior of ICHB was experimentally investigated in the temperature range of 950–1100 °C under isothermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[12] The other process is that iron ore and coals are agglomerated through briquetting and then carbonized in a shaft furnace. [13][14][15][16][17][18] Nippon Steel Corporation [19] prepared iron coke by coke oven process and carried out production tests in industrial coke oven. Meanwhile, Nomura et al [10] studied the influence of iron coke on the BF ironmaking using blast furnace inner reaction simulator (BIS) furnace.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the interaction of SOP and ASP can improve the cold strengths of ferro‐coke before and after carbonization. Wang et al have found that the mechanical strength of the iron coke before carbonization can be notably enhanced by hot briquetting the mixture of iron ore and coal without using binder, but the temperature of the mixtures is relatively high. At the same time, the mechanical strength of iron coke after carbonization can be optimized by adjusting the ratio of coal and iron ore.…”
Section: Introductionmentioning
confidence: 99%